2010
DOI: 10.1155/2010/791625
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of Anatomical and Limited Hepatectomy for Regional Hepatolithiasis

Abstract: Aim. Determination of first line treatment with limited hepatectomy or Anatomical hepatectomy provides better clinical outcome. Methods. Immediate and long-term outcomes of 106 patients who underwent partial hepatectomy for RH at our institution from January 2001 to February 2005 were analyzed retrospectively. Clinical end-points included time to recovery of hepatic function, residual stones, infection of the liver remnant, bile leakage, recurrent stones, morbidity, and mortality. Results. LH was performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
(18 reference statements)
0
12
0
1
Order By: Relevance
“…However, the frequency of left-sided involvement in the present study was lower than those reported by Chen et al (77%) 19 and Jiang et al (72%). 20 This difference reflects the higher frequency of bilateral involvement in the present series (38%). Most of the published series 8,17,18 had shown left lateral segmentectomy to be the predominant type of hepatic resection for the management of RPC.…”
Section: Discussionmentioning
confidence: 54%
“…However, the frequency of left-sided involvement in the present study was lower than those reported by Chen et al (77%) 19 and Jiang et al (72%). 20 This difference reflects the higher frequency of bilateral involvement in the present series (38%). Most of the published series 8,17,18 had shown left lateral segmentectomy to be the predominant type of hepatic resection for the management of RPC.…”
Section: Discussionmentioning
confidence: 54%
“…However, the frequency of left hepatolithiasis in the present series (57.7%) was lower than those reported by Chen et al 36 . (77%) in a series of 103 patients and Jiang et al 37 . (72%) in 106 patients.…”
Section: Discussionmentioning
confidence: 85%
“…(20) suggested that anatomical hepatectomy may reduce the incidence of postoperative complications and postoperative recurrence for patients with hepatolithiasis. A study by Jiang et al (21) suggested that anatomical hepatectomy for treatment of hepatolithiasis was associated with fewer residual stones, fewer infections, and a lower incidence of bile leakage.…”
Section: Mini-reviewmentioning
confidence: 99%